Feasibility and acceptability of saliva-based testing for the screening of SARS-CoV-2 infection in prison - Parodi, Chiara; Ottaviano, Emerenziana; Cocco, Nicola; Ancona, Silvia; Bianchi, Silvia; Massa, Valentina; Bartolotti, Raffaella; Pezzoni, Barbara; Giuliani, Ruggero; Borghi, Elisa; Ranieri, Roberto (Frontiers in Public Health, 2022)
Background Saliva molecular tests have shown a similar sensitivity and specificity compared to nasopharyngeal test for SARS-CoV-2 diagnosis in both symptomatic and asymptomatic individuals. The SARS-CoV-2 pandemic affected Lombardy prisons, generating the need for extensive contact tracing activities and for detecting asymptomatic carriers. The availability of a less invasive test in a setting that hosts a high-risk and often hard-to-reach population, suggests its possible use in prisons. Methods The study was carried out on a population of new incomers in Milan San Vittore pre-trial prison. All the new incomers were submitted to quarantine and to saliva test and nasopharyngeal swab (NPS) for SARS-CoV-2 detection at the entry and at the end of quarantine before their admission in community (Protocol 1–February 2nd to March 5th, 2021). Starting from March 8th to July 30th, 2021, the screening protocol was adjusted to avoid biases in sample collection (Protocol II), and saliva testing was performed at entrance. Results 12/1120 enrolled subjects were excluded from the study. Among the 1080 processed samples, 1 tested positive, 5 weakly positive, 1069 negative, 3 were invalid, and 2 samples tested positive for the viral gene N2 only, with Ct value above 38. During Protocol I, 6/156 coupled saliva/NPS tests were discordant due to food ingestion prior saliva collection, prompting us to establishing Protocol II. Conclusions Saliva molecular testing is feasible in prison setting, being less invasive and easier to use, and reliable. Acceptability was very high even in a complex context as that of newly incarcerated persons.